Associations of dietary factors with gastric cancer risk: insights from NHANES 2003–2016 and mendelian randomization analyses - Zhang, Yigang; Wang, Sen; Li, Qingya; Liu, Hongda; Xuan, Zhe; Li, Fengyuan; Li, Zheng; Xia, Yiwen; Jiang, Tianlu; Xu, Penghui; Fang, Lang; Wang, Linjun; et al. (Frontiers in Genetics, 2024)
Background: Gastric cancer (GC) continues to be one of the leading causes of cancer-related deaths globally. Diet significantly influences the incidence and progression of GC. However, the relationship between dietary intake and GC is inconsistent. Methods: A study was conducted with adults who participated in the National Health and Nutrition Examination Survey (NHANES) from 2003 to 2016 to investigate possible associations between 32 dietary factors and GC. To further detect potential causal relationships between these dietary factors and the risk of GC, a two-sample Mendelian randomization (MR) analysis was conducted. The primary method employed was the inverse variance weighted (IVW) analysis, and its results were further validated by four other methods. Results: Of the 35,098 participants surveyed, 20 had a history of GC. Based on the results of weighted logistic multivariate analysis, it was observed that there was a positive correlation between total fat intake [odds ratio (OR) = 1.09, 95% confidence interval (CI): (1.01–1.17), p = 0.03] and GC as well as negative association of dietary monounsaturated fatty acids (MUFAs) intake [OR = 0.83, 95% CI: (0.76–0.92), p < 0.001]. Further evaluations of the odds of GC across the quartiles of dietary MUFAs showed that the top quartile of total MUFA intake was associated with a lower likelihood of GC in three different models [model1: OR = 0.03, 95% CI: (0.00–0.25), p < 0.01; model2: OR = 0.04, 95% CI: (0.00–0.38), p = 0.01; model3: OR = 0.04, 95% CI: (0.00–0.40), p = 0.01]. For the MR analyses, genetic instruments were selected from the IEU Open GWAS project; IVW analysis showed that GC risk was not associated with MUFAs [OR = 0.82, 95% CI: (0.59–1.14), p = 0.23] or the ratio of MUFAs to total fatty acids [OR = 1.00, 95% CI: (0.75–1.35), p = 0.98]. Similar results were observed when using the other MR methods. Conclusion: The NHANES study revealed that consuming MUFAs was linked to a lower risk of GC, although the results of MR analyses do not provide evidence of a causal relationship. Additional research is therefore necessary to clarify these findings.